Socioeconomic disparities in Plasmodium falciparum infection risk in Southern Malawi: mediation analyses - Solomon T. Wafula; Oumou Maiga-Ascofare; Nicole S. Struck; Don P. Mathanga; Lauren M. Cohee; Jürgen May; Dewi I. Puradiredja; Eva Lorenz (Scientific Reports)
Abstract This study investigated the mediators of the association between socioeconomic position (SEP) and Plasmodium falciparum (Pf) infection in Southern region of Malawi. We utilized data from the 2014 International Center of Excellence for Malaria Research (ICEMR) surveys from Malawi in which blood samples of all individuals from selected households in Blantyre, Thyolo and Chikhwawa were tested for Pf parasitemia. We assessed household SEP and potential mediators – housing quality, food security, education status of household heads, and use of long-lasting Insecticide-treated nets (LLINs) and nutritional status. We conducted causal mediation analyses to assess the proportion of SEP effect that is attributed to each mediator and combination of mediators. The mediation analysis shows that during the rainy season, improved housing and educational attainment explained 39.4% and 17.0% of the SEP effect on Pf infection, respectively, and collectively 66.4%. In the dry season, housing, educational attainment, and LLIN usage collectively mediated 33.4% of SEP’s effect with individual contributions of 15.6%, 11.2%, and 3.8%, respectively. Nutrition also played a role, particularly for children, mediating 9.2% of SEP’s effect in the rainy season and 3.7% in the dry season. The study concluded that multifaceted interventions targeting housing, education, LLIN usage, and nutrition are vital to reducing socioeconomic disparities in Pf infection risk in the Southern region of Malawi.